Eccrine hidradenoma of the breast: distinct pathological lesion mimicking a carcinoma - Olfa El Amine El Hadj; Marwa Mhiri; Aida Goucha; Jameleddine Ben Hassouna; Olfa Adouni; Khaled Rahal; Ahmed El May; Amor Gamoudi (Our Dermatology Online, 2016)
Eccrine hidradenoma (EH) is a rare benign cutaneous neoplasm, believed to arise from the distal excretory duct of the eccrine sweat glands. We report an exceptional lesion of eccrine hidradenoma localized to the breast and clinically mimicking a carcinoma of the breast. Aim: We aim to describe the pathological characteristics of this lesion. We report the case of a 59 year old woman. She presented with a right-sided breast nodule. Physical examination, found a mobile firm nodule retracting the skin. By ultrasound examination, the tumor was heterogeneous and measured 11 mm in great diameter. A local surgical excision of the nodule was performed. By histological exam, the diagnosis of EH was retained. The complement of immunohistochemistry was not requested. This tumor is usually confined to the dermis or subcutaneous layer without. EH of the breast is an uncommon site. Histopathological confirmation is necessary and wide excision of these tumors is the treatment of choice.